Pasteurization time and its response in the chemical characteristics and antioxidant capacity of aguamiel from Agave americana L. - Chagua Rodríguez, Perfecto (2020)
At present, the increase in degenerative diseases such as cardiovascular diseases, cancer and diabetes, demand the frequent consumption of foods with great antioxidant potential that help to inhibit the effect of free radicals. The objective of the present investigation was to evaluate the pasteurization time and its response in the chemical characteristics, the antioxidant capacity and the degradation kinetics of the phenolic compounds of the aguamiel of Agave americana L. The aguamiel was collected from plants with ten to twelve years during the month of April in Acobamba, Huancavelica-Peru. For the analytical determinations fresh and pasteurized aguamiel was conditioned at 80°C for 10, 30 and 45 minutes. Methods described by the AOAC and for the antioxidant capacity the DPPH radical were used. The antioxidant capacity of fresh mead was 40.03% DPPH inhibition and 42.03% at 80 °C for 10 minutes of pasteurization, the heat treatment increased reducing sugars from 11.38% to 25.39%, concentrations of β-carotene and vitamin C expressed decrease due to pasteurization. The degradation kinetics were of order 0 for β-carotene, vitamin C and antioxidant capacity and first order for reducing sugars. It is concluded that the optimal pasteurization time of aguamiel of Agave americana L must be less than 30 minutes.